KONSEP KAFA’AH PERNIKAHAN DIKALANGAN KOMUNITAS SAID/SYARIFAH (Studi Komunitas Said/Syarifah di Kota Medan, Sumatera Utara) - Sirait, Dzakiyyatul Ilmi; Rokan, Mustapa Khamal (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
This study aims to examine the application of the concept of kafa'ah in marriage among the dzurriyat prophets in Medan city, known as said and sharifah. Although Islamic law does not regulate kafa'ah to enter into marriage, if it is studied from an Islamic point of view it is very good to apply, with the aim of forming a sakinah, mawaddah and rahmah family. Kafa'ah is applied among said and sharifah of Medan city in order to guard and care for the lineage of the descendants of the Prophet Muhammad SAW. This research is an empirical juridical research, namely through a social approach with a point case approach through a case approach that occurs in reality. The results of this study concluded that the concept of kafa'ah in marriage among said and sharifah communities in Medan city is different from marriages in general, where the bride and groom must be from said and sharifah circles. If a said or sharifah marries someone who is not from their circle, they will get social sanctions.